A case of disproportionate macrodactyly or a mild form of Proteus syndrome? An interesting case - Abdullah, Shalimar; Haflah, Nor Hazla Mohd; Sapuan, Jamari; Das, Srijit (Acta medica (Hradec Kralove), 2010)
We present a 20-year-old Malay male whom we believe has Proteus syndrome, a rare congenital disorder of asymmetrical overgrowth of body tissues. There are fewer than 100 confirmed cases reported worldwide thus the clinical presentation and histopathological findings are of significance. Our patient presented with an overgrown right small finger and subcutaneous purplish pigmentation over his left upper arm and chest since birth. His small finger gradually increased in size. He had no abnormalities in sensation or power. Radiographs revealed a delta shaped middle phalanx of the small finger. His activities of daily living were uninterrupted but he requested debulking surgery for cosmetic reasons. Histopathological examination reported hypertrophic fatty tissue composed of well formed lobules of mature adipocytes interspersed with fibrous elements.
Keywords: Young Adult; Fingers; mladý dospělý; Humans; mužské pohlaví; prsty ruky; lidé; Male; Proteus Syndrome; Proteův syndrom